Pengaruh the Big Five Personality terhadap Organizational Citizenship Behavior (OCB) dan Kinerja Perawat di Rumah Sakit Santa Clara Madiun - Soepono, Desi Natalia (JRMA | Jurnal Riset Manajemen dan Akuntansi, 2016)
Nurse performance shows the magnitude of the contribution made by nurses to hospital and reflects the performance of a hospital because patient will often relates and meets the nurse. One factor that affect the nurses performance is organizational citizenship behavior (OCB). OCB is extra-role behavior that nurses are willing to do tasks outside of their job discription and the big five personality is one of the factors that significantly influence the OCB. This study aims to examine the direct and indirect influence of the big five personality to the performance of nurses at Santa Clara Madiun Hospital through OCB as intervening variable. The sampel of this research were all nurses at Santa Clara Madiun Hospital. Data collection instruments using questionnaires. Data analysis techniques included descriptive statistics, test data quality, classical assumption, hierarchical regression analysis, and path analysis using SPSS 17.0. The result showed that the big five personality significant positive effect on nurses performance, the big five personality significant positive effect on OCB, and OCB significant positive effect on the nurses performance. OCB has a full mediation effect to influence of the big five personality to the nurses performance.